SGBIT: sistema gerenciador para bibliotecas de Itacoatiara - Rodrigues, Helton Pinheiro da Silva (Brasil, 2019)
Routine changes in the technological landscape cause changes in the habits of society, as with the advancement of technology, competitiveness among companies or service sectors increases, in order to provide improvements in work or services. With this, automation helps and make the processes more efficient. Therefore, this work aims to develop a Management System for Libraries of Itacoatiara - AM, aimed at a Public School of the Municipality. As for the methodology, we used: bibliographic survey, requirements analysis, implementation, system evaluation and finally, the implementation. From the usability analysis, it can be concluded that the SGBIT system is important to help the library management, since it optimizes the work making it more efficient, thus, it is believed that the SGBIT will be of great value. for those responsible for libraries in the public school system of the municipality of Itacoatiara - AM.